The Barriers in Integrating Higher Order Thinking Skills in Indonesia Context - Agung Kurniawan (Jurnal Bahasa dan Sastra, 2020)
Abstract: The 21st century learning requires students to be critical, creative, collaborative and communicative which considered as Higher Order Thinking Skills (HOTS). These skills would help students to compete in the real workforce in the future. However, even though HOTS have been an issue for years, problems still appear in Indonesia as showed in some international measurement. Regarding the discrepancy between the importance of HOTS in learning process and the fact in the field, this paper highlights the barriers in integrating HOTS in English language teaching in Indonesia context. Based on reviewing several related literatures, it could be generalized that the problems in implementing HOTS come from the teachers and the students. Keywords: higher order thinking skills integration, English language learning, Indonesia context Abstrak: Pendidikan pada abad-21 menekankan siswa agar menjadi kritis, kreatif, kolaborative dan komunikatif yang dianggap sebagai kemampuan berpikir tingkat tinggi (HOTS). Kemampuan ini akan membantu siswa untuk berkopetisi dalam dunia kerja nantinya. Tetapi meskipun HOTS telah menjadi isu akhir-akhir ini, masalah tetap saja muncul di Indonesia sebagaimana ditunjukkan dalam beberapa penilaian internasional. Mengenai permasalahan yang muncul dan akan pentingnya HOTS dalam proses pembelajaran Bahasa Inggris, makalah ini akan membahas rintangan yang dihadapi dalam mengintegrasikan HOTS dalam kegiatan pembelajaran Bahasa Inggris di Indonesia. Berdasarkan telaah literatur yang dilakukan, didapatkan bahwa masalah dalam mengimplementasikan HOTS datang dari guru dan siswa. Kata-kata kunci: integrasi kemampuan berpikir tingkat tinggi, pembelajaran Bahasa Inggris, kontek Indonesia